2015
DOI: 10.1186/s12903-015-0026-6
|View full text |Cite
|
Sign up to set email alerts
|

Pathological periodontal pockets are associated with raised diastolic blood pressure in obese adolescents

Abstract: BackgroundObesity, a well-known risk factor for developing cardiovascular disease (CVD), is associated with chronic periodontitis in adults. This cross-sectional pilot study on obese adolescents was designed to investigate whether periodontal disease in terms of pathological periodontal pockets is associated with raised blood pressure and other risk markers for CVD.MethodsThe study included 75 obese subjects between 12 to 18 years of age, mean 14.5. Subjects answered a questionnaire regarding health, oral hygi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 49 publications
3
23
0
2
Order By: Relevance
“…In addition, periodontal measurements in the excluded studies were based solely on the presence of gingival inflammation (gingivitis), and there were no measurements of pocket depth or bone levels. The study by Zeigler, Wondimu, Marcus, and Modéer () also was excluded due to use of an adolescent patient population and a definition of pocket depths greater than 3 mm as “deep.” In addition, the objective of Zeigler et al was to compare blood pressure to obesity, but the level of thyroid‐stimulating hormone (TSH) was used only as an adjusted confounder for that comparison. Consequently, TSH levels could not be directly assessed to measure the effect of hypothyroidism on periodontal disease.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, periodontal measurements in the excluded studies were based solely on the presence of gingival inflammation (gingivitis), and there were no measurements of pocket depth or bone levels. The study by Zeigler, Wondimu, Marcus, and Modéer () also was excluded due to use of an adolescent patient population and a definition of pocket depths greater than 3 mm as “deep.” In addition, the objective of Zeigler et al was to compare blood pressure to obesity, but the level of thyroid‐stimulating hormone (TSH) was used only as an adjusted confounder for that comparison. Consequently, TSH levels could not be directly assessed to measure the effect of hypothyroidism on periodontal disease.…”
Section: Resultsmentioning
confidence: 99%
“…32 The study by Zeigler et al showed no correlation between BMI, dietary habits, hygiene, and oral hygiene in obese adolescents. 33 However, obese teenagers with gingival pocket depth (PD) ≥4 mm had significantly more points with BOP ≥ 25% and considerably higher systolic blood pressure than obese teenagers with PD < 4 mm. 33 This data may confirm the assumption that periodontal disease in obese adolescents has an impact on organ complications of obesity, leading to the development of arteriosclerosis and cardiovascular diseases.…”
Section: Obesity and Periodontal Diseasementioning
confidence: 99%
“…33 However, obese teenagers with gingival pocket depth (PD) ≥4 mm had significantly more points with BOP ≥ 25% and considerably higher systolic blood pressure than obese teenagers with PD < 4 mm. 33 This data may confirm the assumption that periodontal disease in obese adolescents has an impact on organ complications of obesity, leading to the development of arteriosclerosis and cardiovascular diseases. Also Scorzetti et al noted a significant increase in the values of periodontal disease indicators, including the oral hygiene index (OHI), approximal plaque index (API) and BOP, and a higher percentage of pockets with a probing depth exceeding 4 mm in obese children aged 6-13 compared to peers with normal body weight.…”
Section: Obesity and Periodontal Diseasementioning
confidence: 99%
“…These cells could migrate to the vasculature and kidneys and alter vascular function, promote renal damage and contribute to hypertension. In line with this hypothesis, several studies show the coexistence of periodontal and cardiovascular disease in patients (Tsakos et al ., ; Ricardo et al ., ; Schmitt et al ., ; Winning et al ., ; Zeigler et al ., ; Hansen et al ., ). However, most of these studies suffer from clinical limitations related to confounding factors.…”
Section: Introductionmentioning
confidence: 99%